(untitled) (London, 2002)
In The Origins of Nonliberal Capitalism, German sociologists and American and Japanese political scientists draw extensively on the work of economists and historians from their home countries, as well as from the United Kingdom and France. The contributors discuss the potential disappearance, evolution, and reconstitution of nonliberal capitalism in Germany and Japan by analyzing its historical origins from two perspectives: the emergence and survival of nonliberal capitalism, and the causes of differences between the systems of Germany and Japan. They also outline the requirements for internally coherent national models of an embedded capitalist economy. The histories of German and Japanese capitalism demonstrate that capitalism's structural forms and functional relations evolve by means of different processes with different goals
Keywords: Capitalism,Capitalism,Germany,Japan; Economic policy,Economic policy; Germany,Japan